Kinematical uniqueness of homogeneous isotropic LQC. (5th December 2016) - Engle, Jonathan; Hanusch, Maximilian
Abstract: In a paper by Ashtekar and Campiglia, invariance under volume preserving residual diffeomorphisms has been used to single out the standard representation of the reduced holonomy-flux algebra in homogeneous loop quantum cosmology (LQC). In this paper, we use invariance under all residual diffeomorphisms to single out the standard kinematical Hilbert space of homogeneous isotropic LQC for both the standard configuration space R B o h r, as well as for the Fleischhack one R ⊔ R B o h r . We first determine the scale invariant Radon measures on these spaces, and then show that the Haar measure on R B o h r is the only such measure for which the momentum operator is hermitian w.r.t. the corresponding inner product. In particular, the measure is forced to be identically zero on R in the Fleischhack case, so that for both approaches, the standard kinematical LQC-Hilbert space is singled out.